Depletion of blood supply and cost due to indeterminate donations at the Guillermo Almenara Irigoyen National Hospital - Moya-Salazar, Jeel (2017)
Objective: To evaluate the depletion of blood supply and the cost of indeterminate donations at the Guillermo Almenara Irigoyen National Hospital during 2014. Materials and methods: Retrospective cross-sectional study and cost-utility analysis in donations with gray zone results (sample value/cut-off value between the limits > 0.85 and < 1) after serological screening for the seven infectious markers (HIV, HBsAg, HBcAb, HCV, HTLV-1/2, SYPHILIS and CHAGAS) and simultaneous determination of HIV Ag/Ab combo, by fourth-generation ELISA. The data were coded and tabulated from the e-Delphyn® system. The cost analysis was performed considering the current exchange rate. Results: Out of 9,560 donations, 20.7% (1977 donations) were gray zone results, resulting in a loss of 863.9 liters of blood and 92,640 USD. HbcAb with 10.18% (973 indeterminate results) and anti-HIV with 0.39% (37 indeterminate results) were the results with the highest and lowest seroprevalence, respectively (p<0.05). No significant difference was found between anti-HIV and HIV Ag/Ab combo markers (p=0.776). Conclusions: It was demonstrated that >800 liters of discarded blood generated >90 thousand USD of cost for undetermined donations causing economic damage to the hospital budget and a decrease in the blood supply available for the treatment of patients at the Guillermo Almenara Irigoyen National Hospital.